2019
DOI: 10.1002/adom.201800858
|View full text |Cite
|
Sign up to set email alerts
|

Optical Control of Ferroelectric Domains: Nanoscale Insight into Macroscopic Observations

Abstract: has been investigated for the optical reading of ferroelectric random-access memories, [14,15] photodiodes, [16] and photovoltaic [4,[17][18][19][20][21][22][23] applications. Current research is focused on developing band-gap tuned ferroelectric materials as their performance is restricted by low mobility of charge carriers and short diffusion lengths. [24][25][26] Band-gap tuned ferroelectric materials are capable of hosting multiple functionalities (due to ferroelectricity and semiconducting features), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 37 publications
3
70
0
Order By: Relevance
“…However, in this work, the light source was a 405 nm laser, which only induced a local temperature change of 0.5 C in the KNBNNO. [37,62] Such a change is negligible compared with the nearly 45 C shown in Figure 7b. Therefore, the photovoltaic effect observed in this work was true and was not induced by the pyroelectric effect.…”
Section: Simultaneous Operation Of Photovoltaic and Pyroelectric Effectsmentioning
confidence: 77%
See 3 more Smart Citations
“…However, in this work, the light source was a 405 nm laser, which only induced a local temperature change of 0.5 C in the KNBNNO. [37,62] Such a change is negligible compared with the nearly 45 C shown in Figure 7b. Therefore, the photovoltaic effect observed in this work was true and was not induced by the pyroelectric effect.…”
Section: Simultaneous Operation Of Photovoltaic and Pyroelectric Effectsmentioning
confidence: 77%
“…It has been reported that illumination could change the permittivity and thus capacitance, as well as resistivity and thus resistance, of the KNBNNO. [62] The changed capacitance and resistance could alter the resonant frequency of the KNBNNO element, leading to a reduced output current density (in the same way as shown earlier). [63] This is the reason that the add-on effect of the piezoelectric current density (35 nA cm À2 -positive maximum) and photovoltaic current density (20 nA cm À2 ) did not fulfill the linear superposition (45 nA cm À2 in reality instead of 55 nA cm À2 in theory).…”
Section: Simultaneous Operation Of Piezoelectric and Photovoltaic Effmentioning
confidence: 77%
See 2 more Smart Citations
“…In this context, two novel energy-conversion cycles are proposed in this article by exploring a novel monolithic multifunctional material KNBNNO ((K 0.5 Na 0.5 )NbO 3 -2 mol% Ba(Ni 0.5 Nb 0.5 )O 3Àδ )). [4,5,31] KNBNNO being a bandgap-engineered (1.6 eV) ferroelectric with good piezoelectric and pyroelectric responses is capable of simultaneously utilizing inputs from an external electric field, stress, thermal fluctuation, and light. [4,5,31] Recent work has shown the optical control of ferroelectric domains [31] and DOI: 10.1002/ente.202000500…”
Section: Introductionmentioning
confidence: 99%